Forty healthy and non-pregnant Fries Holland dairy cows which had received oestrus synchronization were divided randomly into four experimental groups. Artificial inseminations (AI) were implemented 8-10 hours post estrous using frozen semen from the same breed. The first three groups were injected with 100, 150 and 200 mg medroxy progesterone acetate (MPA) i.m., respectively, three days post AI, while the other group was injected with placebo as control group. Madura cattle embryos were transfe - Imam Mustofa; Laba Mahaputra; Pudji Srianto; Suzanita Utama (Media Veteriner, 1999)
Forty healthy and non-pregnant Fries Holland dairy cows which had received oestrus synchronization were divided randomly into four experimental groups. Artificial inseminations (AI) were implemented 8-10 hours post estrous using frozen semen from the same breed. The first three groups were injected with 100, 150 and 200 mg medroxy progesterone acetate (MPA) i.m., respectively, three days post AI, while the other group was injected with placebo as control group. Madura cattle embryos were transfered contralaterally seven days post AI. The percentage of pregnancy in groups which had received 100 and 150 mg MPA was 37.5%r, and in group received 200 mg MPA and control was 55.6%, and 60%, (P>0.05), respectively. Calving percentages of the 100, 150, 200 mg MPA and the control groups were 25,37.5,55.6 and 60% respectively (P>0.05). All birth gave single calve.